2013
DOI: 10.1007/s11538-012-9802-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatal or Harmless: Extreme Bistability Induced by Sterilizing, Sexually Transmitted Pathogens

Abstract: Models of sexually transmitted infections have become a fixture of mathematical epidemiology. A common attribute of all these models is treating reproduction and mating, and hence pathogen transmission, as uncoupled events. This is fine for humans, for example, where only a tiny fraction of sexual intercourses ends up with having a baby. But it can be a deficiency for animals in which mating and giving birth are tightly coupled, and mating thus mediates both reproduction and pathogen transmission. Here, we mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The second way in which density-and frequencydependence could interact in two-sex populations is through resource competition [17,18] and other antagonistic intersexual interactions such as harassment [19,20] and disease transmission [21]. Competition occurs both within and between the sexes, and several studies have shown sex differences in competitive ability [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The second way in which density-and frequencydependence could interact in two-sex populations is through resource competition [17,18] and other antagonistic intersexual interactions such as harassment [19,20] and disease transmission [21]. Competition occurs both within and between the sexes, and several studies have shown sex differences in competitive ability [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-dependent incidence is routinely assumed for sexually transmitted diseases (e.g. Thrall et al (1993); Thrall and Antonovics (1997); Boots and Sasaki (2003); Berec and Maxin (2013); Bernhauerová and Berec (2015)). It is also believed to be a suitable description of infection process among animals in herds (Diekmann et al (2012); de Jong et al (1995)) and in vector-borne diseases (Thrall et al (1993); Antonovics et al (1995); Thrall et al (1995)).…”
Section: Si Epidemics With Frequency-dependent Transmissionmentioning
confidence: 99%
“…The system in (10) is a generalization of the model considered in Berec and Maxin (2013). In Berec and Maxin (2013), the authors investigate an epidemiological model of a partially sterilizing, sexually transmitted disease in which they take into account the fact that in sexually transmitted diseases, host population birth rates and the rate of infection transmission are both mediated by the mating process. Assuming that σ ∈ [0, 1] is the probability of not becoming sterile upon infection and that both partners must be fertile to produce offspring, they arrive at…”
Section: Model Imentioning
confidence: 99%
See 1 more Smart Citation